A post-critical perspective to community participation in trans-boundary water governance – A case study of the Volta River Basin in West Africa. (December 2016) - Wong, Sam
Abstract: This paper develops the Post-critical approach to challenge the assumptions of both the Mainstream and the Critical approaches in understanding trans-boundary water management. It argues that local participation in trans-boundary water governance may not necessarily create benefits for poor people. Drawing on the Volta River Basin in West Africa as a case study, it suggests that building new participatory governance structures, based on the existing traditional chieftaincy authority structures, is vulnerable to elite capture. Bringing in democratic institutions, such as the quota system to ensure a minimum numbers of female representatives in the local trans-boundary water committee, overlaps with the old institutions, and that results in reinforcing gender inequalities. The paper highlights the interplay between agency and structure in understanding the potential and the limitations of community empowerment in the trans-boundary water governance.